2019
DOI: 10.2147/ott.s196638
|View full text |Cite
|
Sign up to set email alerts
|

<p>Assessment of tumor mutation burden calculation from gene panel sequencing data</p>

Abstract: Background: High tumor mutation burden (TMB) is an emerging selection biomarker for immune checkpoint blockade in tumors such as melanoma and non-small cell lung cancer. TMB is typically calculated from whole genome sequencing or whole exome sequencing (WES) data. Recently, clinical trials showed that TMB can also be estimated from targeted sequencing of a panel of only a few hundred genes of interest, which can be performed at a high depth for clinical applications. Materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 30 publications
1
35
1
Order By: Relevance
“…The TMB values in our patients, as estimated using the TST170 panel, ranged from 3.8 to 24.8 mutations/Mb. These values were within the range of those found for OC using whole-exome sequencing [29] and FoundationOne [30], although the median values (8.6 mutations/Mb) were higher than those estimated with these methods (3-4 mutations/Mb) [29,30]. The use of a small gene panel and the low number of patients studied may have overestimated the median TMB values [31].…”
Section: Cd137 Expression Is An Indication Of Ongoing or Recent Activsupporting
confidence: 52%
“…The TMB values in our patients, as estimated using the TST170 panel, ranged from 3.8 to 24.8 mutations/Mb. These values were within the range of those found for OC using whole-exome sequencing [29] and FoundationOne [30], although the median values (8.6 mutations/Mb) were higher than those estimated with these methods (3-4 mutations/Mb) [29,30]. The use of a small gene panel and the low number of patients studied may have overestimated the median TMB values [31].…”
Section: Cd137 Expression Is An Indication Of Ongoing or Recent Activsupporting
confidence: 52%
“…Chinese melanoma is mostly the mucosal type while malignant melanomas in Europe and the United States are mostly the skin type, the onset of which is usually the result of accumulation of genomic mutations caused by UV. Accordingly, previous studies have confirmed a higher TMB in skin type malignant melanoma [41,42]. A Chinese tumour patient study as well as a TCGA database study showed that gastric cancer and colorectal cancer also have relatively higher TMBs [41,43], but these studies have not fully demonstrated the impact of dMMR/MSI-H on TMB.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, previous studies have confirmed a higher TMB in skin type malignant melanoma [41,42]. A Chinese tumour patient study as well as a TCGA database study showed that gastric cancer and colorectal cancer also have relatively higher TMBs [41,43], but these studies have not fully demonstrated the impact of dMMR/MSI-H on TMB. In order to provide more accurate information on TMB in different tumour types, our study specifically separated dMMR gastric and colorectal cancers from non-dMMR types Fig.…”
Section: Discussionmentioning
confidence: 95%
“…These findings have also been observed in an independent analysis of the TCGA data set. 28 Currently, gene panels are typically designed to identify actionable point mutations, indels or copy number variants and not to assess overall TMB. Further investigation may show that mutations in some genes are more readily tolerated than others because of functional redundancy, decreased neoantigen presentation due to loss of major histocompatibility complex (MHC) expression or combinations of other mechanisms.…”
Section: Open Accessmentioning
confidence: 99%